Розвиток 3D-технологій в кулінарії - Лущик, Ірина Романівна; Голікова, Тетяна Петрівна (My University, 2017)
Розглянуто характеристику 3D-принтерів для приготування харчових продуктів, принцип роботи харчового 3D-принтеру. Показано переваги застосування технологій 3D-друку у сучасній кулінарії. The characteristics of 3D-printers for production of food products and principle of working of food 3D-printer have been considered. The advantages of applying of technologies of 3D-printing in modern cooking have been presented.
Keywords: стереолітографія; 3D друк; stereolithography; 3D printing; кулінарія; кафедра готельно-ресторанної справи